Genetic analysis of drought tolerance in maize inbred lines: preliminary results - Meseka, S.K.; Menkir, A.; Ibrahim, A. (2007)
Drought stress causes significant yield reduction in maize Zea mays L. grown in sub-Saharan Africa (SSA. An understanding of the inheritance of drought tolerance would be useful in developing drought tolerant hybrids. The objectives of this study were to determine (i) the effects of the level of drought tolerance in parental inbred lines on the performance of their hybrids, (ii) mode of inheritance of drought tolerance in inbred lines selected for contrasting responses to drought, and (iii) relationship between per se performance of the parental lines and their hybrids. A Design ll mating scheme was used to produce96 single-cross hybrids from 24 inbred lines. The parental lines and F1 hybrids were evaluated in separate trials laid out side by side at lkenne, Nigeria in 2002. Both general (GCA and specific (SCA combining abilities were significant (P < 0.01), with GCA accounting for >50% of total variation for all traits except ears per plant under well-watered conditions. These results indicated that additive genetic effects largely influenced grain yield and other traits of the hybrids when evaluated under water stress. Most of the crosses with at least one tolerant parent produced tolerant hybrids, whereas most of the crosses involving two susceptible lines produced susceptible hybrids. Mid-parent values of inbred lines per-se were useful predictors of hybrid performance for all traits except ear aspect scores. Inbred lines KU1409,1824,9006,4001, POP10, and (TZI21501xKU1414x501) could be used as parents for developing drought tolerant maize hybrids. Results of this study led to the conclusion that yield improvement in drought tolerant maize is associated with the level of drought tolerance in parental lines.